Pereduksian COX, NOX, SOX, HC dari Kendaraan Bermotor dengan Menggunakan Plasma Non-Termik - Nur, Muhammad; Wirawan, Bukit Yuta; Adi Wijaya, Wahyu; Suseno, Ahmad; Sumariyah, Sumariyah (BERKALA FISIKA, 2006)
Reduction NOX gas from motor vehicle 1486 cc emission have been done by using corona glow discharge plasma which awakened with power source from modified system ignition of car.NOX Gas is result emission of motor vehicle 1486 cc at 2000 rpm. Flow NOX source are joined with reactor. Corona glow discharge plasma awakened in the reactor with knife to plane electrode geometry configuration with power source from modified system ignition of car. Corona that happened in reactor which containing of motor vehicle gas emission 1496 cc will yield ion, electron, and energetic radical. NOX will turn into compounds which do not dangerous and it’s indicate that pollutants in reactor was reduced.  To get the decomposition efficiency of NOX it’s require to be done the measurement of concentration of NOX before and after reduced. The biggest decomposition efficiency of NOX which obtained in this research is 81.38 % at distributor rotation equal to 1500 rpm with current equal to 80µA. Anion and cation analysis show there are cation NH4+ and anion CO32-, SO32-, and SO42-, that giving hypothesize that one of compiler compound of crust result of system prototype to reduce NOX are ammonium carbonate ((NH4)2CO3), ammonium sulfide ((NH4)2SO3), and ammonium sulphate ((NH4)2SO4).